Cognitive universals and cultural variation in teaching. (2015) - Strauss, Sidney; Ziv, Margalit; Frye, Douglas
Abstract: We address three issues: (1) There is a need for a comprehensive multidisciplinary understanding of teaching; (2) teaching is a natural cognitive ability for humans; and (3) there is a need to incorporate the mentalistic and cultural approaches to teaching. We suggest certain research studies that can help deepen our understanding of the cognition of teaching.